An investigation into the use of intensive therapy, with and without constraint-induced movement therapy, in South African children with hemiplegia - Geretto, Esther (Division of Physiotherapy, 2017)
This research project aimed to determine whether a two-week period of intensive physiotherapy in groups, using the Neurodevelopmental Approach or Constraint Induced Movement Therapy (CIMT), would result in a functional improvement in the hand function of children with hemiplegia. It also aimed to determine if group CIMT was more effective than group physiotherapy based on the Neurodevelopmental (NDT) approach. The feasibility of CIMT in the South African context was also investigated Sixty-five children with hemiplegia were requested to participate in the research study at the Red Cross Children's Hospital in Cape Town, South Africa. Twelve of these patients eventually participated in the study. They were divided into CIMT and NDT based physiotherapy groups. Both groups received intensive physiotherapy for a period of two weeks (every day for two hours). The non-affected upper limb of the CIMT group was restrained with a glove, whilst the NOT based physiotherapy group was unrestrained. The children were assessed before therapy, directly after therapy at two weeks, using the Peabody Developmental Fine Motor Scale and kinematic analysis (Vicon Clinical Manager), and again one month later using the Peabody Developmental Fine Motor Scale. The results showed that the children (in both the CIMT and NDT-based physiotherapy groups) demonstrated a significant improvement in grasp function (with a change in median grasp score from 28.5 to 33.0, p<0.02) and visual motor integration (with a change in median VMI score from 71.0 to 78.0, p<0.02) following two weeks of intensive physiotherapy and that this improvement in function was maintained for a month following therapy. There did not appear to be any benefit of group CIMT over that of NDT based physiotherapy - however this is said with caution due to the small sample size. Through the questionnaire and informal interviews, it was felt that CIMT in its' current form was not feasible for use in the South African context, mainly due to lack of financial and human resources. Further research is recommended to determine whether a different mode of CIMT therapy would be more feasible in the South African context. However, it was felt that due to the improvement seen after two weeks of group intensive physiotherapy, an attempt should be made to integrate periodic sessions of intensive group therapy into local community settings, particularly in the South African context of inadequate resources, to provide regular therapy to children living in rural areas.